A Closed-Loop Economy in the Meat Industry for Generating Alternative Energy from Biogas Plants - Elżbieta Jadwiga Szymańska; Robert Mroczek; Jadwiga Drożdż (Energies)
This study deals with the concept of a closed-loop economy in the meat industry through the use of animal by-products in biogas plants for electricity generation processes. The purpose of the study was to identify the volume of by-products from the slaughter of cattle and pigs, how the by-products are managed, and the efficiency of their use in biogas plants for electricity production processes. The analyses used data from the Central Statistical Office, the Chief Veterinary Inspectorate, and information obtained from the Polish Agency for Enterprise Development. Studies from the literature on closed-loop economies and bioeconomies were also a valuable source of information. Based on case studies, this paper also presents examples of a closed-loop economy in meat companies. In the area of pork, poultry, and beef livestock production, the analysis covered the years 2004–2022, while in the area of the production and use of meat industry by-products, the data came from 2017–2022. The study shows that reducing the production of waste in the meat industry and the reuse and recycling of waste are important parts of a closed-loop economy. In meat companies, waste from slaughtering animals can be properly managed, either by processing it into animal feed or by using it in biogas plants to generate electricity or heat. Taking into account the number of by-products from cattle and pig slaughter in the country, biogas plants could produce approximately 95,232 MW of electricity per year, which constitutes approximately 4.3% of the energy intensity of the meat industry in Poland.